FILTER MODELING METHODS AND STABLE AND UNSTABLE BEHAVIOR OF GROUNDWATER IN AQUIFERS - Sabirova, Zebunisa Ozatovna (INTERNATIONAL CONFERENCES, 2023)
This article filtering modeling mainly used hydraulic and electrical analogies implemented in solid and lattice models. Rigid hydraulic models represented by various types of filter trays have been used in hydrogeological calculations.